The Ligand-Binding Domain of Siglec-G Is Crucial for Its Selective Inhibitory Function on B1 Cells - Hutzler, Stefan; Özgör, Lamia; Naito-Matsui, Yuko; Klaesener, Kathrin; Winkler, Thomas; Reth, Michael; Nitschke, Lars (Journal of Immunology, 2014)
Siglec-G is an inhibitory receptor on B1 cells. Siglec-G-deficient mice show a large B1 cell expansion, owing to higher BCR-induced Ca2+ signaling and enhanced cellular survival. It was unknown why Siglec-G shows a B1 cell-restricted inhibitory function. With a new mAb we could show a comparable Siglec-G expression on B1 cells and conventional B2 cells. However, Siglec-G has a different ligand sialic acid-binding pattern on peritoneal B1 cells than on splenic B cells, and its sialic acid ligands are expressed differentially on these two B cell populations, suggesting that cis-ligand binding plays a crucial role on B1 cells. This observation was further studied by generation of Siglec-G knockin mice with a mutated ligand-binding domain. These mice show increased B1 cell numbers, increased B1 cell Ca2+ signaling, better B1 cell survival, and changes in the B1 cell Ig repertoire. These phenotypes are very similar to Siglec-G-deficient mice. The mutation of the ligand-binding domain of Siglec-G strongly reduces the Siglec-G-IgM association on the B cell surface. Thus, Siglec-G sialic acid-dependent binding to the BCR is crucial for the B1 cell-restricted inhibitory function of Siglec-G and is regulated in an opposite way to that of the related protein CD22 (Siglec-2) on B cells.